The Influence of Profitability, Leverage, and Sales Growth on Tax Avoidance in Non-Cylical Consumer Sector Companies - Claudia Triana; Florencia Irena Lawita; Adeline Milagros (Universitas Pelita Harapan, 2024)
Tax avoidance is a form of tax avoidance that does not exceed applicable legal boundaries and tax regulations. Tax avoidance is implemented by looking at the gaps and weaknesses in tax regulations. The aim of this research is to test whether profitability, leverage and sales growth indicators are able to influence tax avoidance. The research was conducted on companies in the non-cyclical consumer sector listed on the Indonesia Stock Exchange for the period 2020 - 2022. The research method used was a quantitative method with purposive sampling. The author used SPSS version 27 software to process the data. The results of this research are that profitability and sales growth influence tax avoidance. Meanwhile, leverage has no effect on tax avoidance.